2018
DOI: 10.1055/s-0038-1669465
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomic Study of the Facial Nerve Trunk and Branching Pattern in an African Population

Abstract: There are known racial variations in the branching and furcation pattern and the length of the facial nerve (FN) trunk and hardly any studies from the black African population. Surgeries around the FN predispose it to trauma and warrant a detailed anatomy of its branching pattern. Using a descriptive cross-sectional study, a total of 40 FN (20 fresh cadavers) were dissected to record the pattern and length of the FN. The frequency of various patterns of FN using the Davis et al classification was as follows: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 24 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…The reported incidence of the FNT bifurcation is about 80%, the trifurcation -14% and numerical variants are found in 6% [8,[18][19]. In the current study the bifurcation of the FNT was established in 84% of cases (including 6.7% of number variation), trifurcation was established in 6.6% and multifurcation in 9.4% of cases.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The reported incidence of the FNT bifurcation is about 80%, the trifurcation -14% and numerical variants are found in 6% [8,[18][19]. In the current study the bifurcation of the FNT was established in 84% of cases (including 6.7% of number variation), trifurcation was established in 6.6% and multifurcation in 9.4% of cases.…”
Section: Discussionsupporting
confidence: 50%
“…In the current study the bifurcation of the FNT was established in 84% of cases (including 6.7% of number variation), trifurcation was established in 6.6% and multifurcation in 9.4% of cases. In cases of the facial canal dehiscence a double or triple FNT is present [8,15,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, the study conducted by Weerapanta et al showed that type V is the most frequent in the Thailand population [25]. Thuku et al concluded type I as the most common in the African population [26]. Rana et al, Quadros et al, and Bendella & colleagues found type II as the most common in Pakistan, Indian, and German subjects, respectively [27-29] (Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies were conducted in Asia, [11][12][13][14][15][16][17][18][19][20][21][22][23][24] three in the USA, 5,25,26 three in Europe, 8,27,28 and one in Africa. 29 All studies were published between 1956 and 2019. The number of specimens in each study ranged from 20 to 350.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the Quality Appraisal for Cadaveric Studies scale, the study with the highest reliability was that of Thuku et al, scoring 13 of 13 points, 29 followed by the study by Stankevicius and Suchomlinov with 12 of 13 points. 28 The study with the lowest methodological quality was that by Quadros et al with 5 of 13 points.…”
Section: Resultsmentioning
confidence: 99%